2018
DOI: 10.30637/2018.16-030
|View full text |Cite
|
Sign up to set email alerts
|

An Aicardi-Goutières syndrome associated with a quasi-Moyamoya by a biallelic mutation in SAMHD1

Abstract: SAMHD1 is one of seven known genes responsible for Aicardi-Goutières syndrome. It has the particularity to associate to this rare pediatric encephalopathy with autoimmune manifestations, a cerebral vasculopathy type Moyamoya. This condition has only been recently reported, less than fifty times in the literature. Our clinical case is a 11 year old boy from an inbred union whose clinical diagnosis confirmed genetically and followed by a review of current data determined an ad hoc management, presently described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…20 The incidence of AGS-5 is rare, and different allelic variants of the SAMHD1 gene have been identified. [7][8][9]11,15,16,21,22 Common clinical manifestations are progressive neurological dysfunction, poor feeding, and irritability. 22 Our case had arterial vasculopathy confirmed by MRI on the eleventh day after birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 The incidence of AGS-5 is rare, and different allelic variants of the SAMHD1 gene have been identified. [7][8][9]11,15,16,21,22 Common clinical manifestations are progressive neurological dysfunction, poor feeding, and irritability. 22 Our case had arterial vasculopathy confirmed by MRI on the eleventh day after birth.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review on arteriopathy in AGS, we identified 12 cases described by five authors. [7][8][9][10][11] The blood relation was not encountered in nine individuals, consanguinity was observed in two children, and the third patient with possible consanguinity was born to Old Order Amish parents. Seven patients were female.…”
Section: Additional Cases and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that MMD might be a mitochondria-related disease [72]. There are other well-known vasculopathies that are caused by impaired nucleotide processing, such as Aicardi-Goutières syndrome that is caused by mutations in the ribonuclease RNASEH2, the exonuclease TREX1, or the deoxynucleoside triphosphate triphosphohydrolase SAMHD1 [73][74][75], or such as SLE that is triggered by autoimmune responses to toxic DNA or also to mtRNA [76][77][78][79]. It is therefore conceivable that they share pathogenetic mechanisms with MMD, which may have to be classified among them.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases of moyamoya have been reported in patients with Turner’s syndrome [ 94 , 193 ]. In our literature search, we found one case of moyamoya with Aicardi Goutieres syndrome [ 194 ].…”
Section: Reviewmentioning
confidence: 99%